Assessment of preoperative serum albumin level and its correlation with postoperative wound complication in major elective abdominal surgeries - Ramole, Yashpal; Chaudhary, Anuradha; Patel, Badri Prasad; Divan, Abhijeet Singh; Jain, Amit; Songra, M. C. (International Surgery Journal, 2020)
Background: Patients who have signs of malnutrition have a higher risk of complications and an increased risk of death in comparison with patients who have adequate nutritional reserves. It is common and occurs in about 30% of surgical patients with gastrointestinal diseases and in up to 60% of those in whom hospital stay has been prolonged because of postoperative complications. The serum albumin level is the most readily available and clinically useful parameter. A serum albumin level greater than 3.5 g% suggests adequate protein stores and it confers a protective effect through several biological mechanisms. It predicts perioperative morbidity and mortality. Methods: Our study was conducted on a cohort of 100 Patients admitted in Department of General surgery Hamidia Hospital for major elective surgery between October 2016 and September 2017. Sample size taken was 100. Results: The present study shows that patients with serum albumin less than 3 g/dl has more postoperative complications and patients with serum albumin >3.5 g/dl has less postoperative complications which was statistically significant. The study concludes that as the serum albumin level increases the complication rate decreases. Conclusions: Our study shows that sr. albumin is a good indicator of postoperative complications. The patients with sr. albumin <3.0 g/dl had a higher complication rate which was statistically significant (p<0.05). Patients with sr. albumin >3.5 g/dl had less complications which was statistically significant (p<0.05). The correlation between the serum albumin and complication rate was statistically significant in the malignant diseases when considered separately.